The Promise and Peril of Big Data in Driving Consumer Engagement - Vasilopoulou, Christina; Theodorakopoulos, Leonidas; Igoumenakis, Giorgos (Technium Social Sciences Journal, 2023)
The advent of big data has transformed the way in which businesses interact with consumers. With the ability to collect and analyze vast amounts of data from multiple sources, companies are now able to gain insights into consumer behavior that were previously impossible. This paper explores the relationship between big data, consumer behavior, digital marketing and personalizing the customer experience. It examines the ways in which big data is being used to gain insights into consumer behavior, the benefits and limitations of using big data, ethical considerations and the role of digital marketing in leveraging big data to create more effective marketing strategies.